ANALISIS KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL) PADA PT BANK TABUNGAN NEGARA PERSERO TBK DAN PT BANK MANDIRI PERSERO TBK - Tommy Munaf; Lulu Vriska Rianti; Vanisa Meifari; Nurfitri Zulaika (Juremi: Jurnal Riset Ekonomi, 2023)
Abstract This study aims to determine the soundness level of Bank BTN and Bank Mandiri for the 2018-2021 period in terms of the overall RGEC (Risk Profile, Good Corporate Governance (GCG), Earning, Capital) aspects. This type of research is quantitative descriptive with research subjects in the form of Bank BTN and Bank Mandiri which are listed on the Indonesia Stock Exchange in 2018-2021. The data collection technique in this study was to use literature and documentation. The data analysis technique used is the soundness analysis of the bank with the assessment including RGEC factors. The results of this study show that the final RGEC score at Bank BTN for the 2018-2021 period is 80.00, 70.00, 70.00, 73.00, respectively. The results in 2018 are in the healthy category because they are in the range of 71-85. In 2019-2020 it is in the category of quite healthy because it is in the range of 61-70. In 2021 it will return to a healthy predicate. Meanwhile at Bank Mandiri for the 2018-2021 period it was 87.00, 87.00, 90.00, 90.00 respectively. All of these results are in the very healthy category, because they are in the range of 86-100. Based on the results of the study, it can be concluded that the health of Bank BTN and Bank Mandiri which are listed on the Indonesia Stock Exchange using the RGEC method for 2018-2021 are in an unstable position with the title of quite healthy, healthy, to very healthy